A novel approach to investigating 3D fracture connectivity in ultrahigh steep rock slopes. (January 2023) - Zhang, Yansong; Chen, Jianping; Zhou, Fujun; Zhang, Wen; Yan, Jianhua; Li, Yuchao; Li, Zhihai; Zhao, Mingyu; Xu, Wanglai; Liu, Yongqiang; Wang, Qing
Abstract: Ensuring the high-quality construction of the ST Railway is a top priority for construction organizers and managers. In this paper, a stepwise approach combining bounding box (BB) technology and the Gilbert–Johnson–Keerthi (GJK) algorithm was proposed to determine the intersections between fractures. With the use of a stepwise approach, most of the nonintersecting fracture pairs were excluded, the computed speed and effectiveness were greatly improved compared with those in previous studies, and the length and direction vectors of the fracture intersections were obtained. A 3D discrete fracture network (DFN) model was generated and validated according to fracture data acquired from the right bank slope of the Nujiang Grand Bridge (NGB) of the ST Railway by unmanned aerial vehicle (UAV) photogrammetry technique. Based on the DFN model, the stepwise approach was implemented for intersection analysis and connectivity analysis. Connectivity parameters, including the number of intersections per unit volume and the intersection length per unit volume, were calculated as 1.279 m -3 and 2.296 m -2, respectively. The intersection analysis suggested that the mean length of the intersections was 1.796 m, and fracture sets 2 and 3 constituted the main flow pathways and played a predominantly combined cutting role for the rock masses in the study area. In addition, the investigation of the direction vector of the intersections indicated that the combined cutting action of fracture sets 2 and 3 easily formed wedge-shaped failure surfaces, and the lateral expansion produced by bedrock fracture groundwater was also unfavourable to the stability of the slope. Highlights: A stepwise approach combining BB technology and the GJK algorithm was proposed. A 3D DFN model was generated based on fracture data obtained by UAV photogrammetry. The hydraulics and stability of the rock mass in the rock slope were investigated.